Effect of certain plant growth regulators on callus induction and Organogenesis of Alternanthera sessielis in vitro - Al-Aradi, Haleemah J. (Iraqi Journal of Aquaculture, 2016)
Propagation of Alternanthera Sessiels in vitro by callus induction through the culture of adventitious bud on MS medium supplemented with 2.4-D and NAA in 1.5mg/L, primary callus where transferred on MS medium supplemented with 0.5mg/L Benzyl Adenine (BA) and 0.5mg/L Kinetin (Kin) for induction Adventitious shoot, somatic embryos appeared when primary callus transferred to free hormones MS medium, Effects of cytokinins in direct organogenesis with various concentration was also examined, the fourth treatment 1mg /L Kin+1mg/L BA give significant Increase , and scored the highest mean of shoot number 12 shoot. Also fourth treatment caused significant increase and gave highest mean of shoot length 5.33cm, while no significant different was appeared between the fourth treatment and 1mg/L Kin in the number of vegetative bud. Fourth treatment also scored significant increased in the number of flower and give 5.33 flower/node, Direct and indirect regenerated shoot were transferred to half strength MS medium supplemented with 0.5 mg /L NAA+ 0.5 mg/L IBA for root induction, plantlet were transferred to water field after successful acclimatization.